2019
DOI: 10.1136/annrheumdis-2018-214335
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of neutrophil extracellular traps (NETs) in patients with Behcet’s disease

Abstract: ObjectivesBehçet’s disease (BD) is a chronic systemic vasculitis. Thrombosis is a frequent and life-threatening complication. The pathogenesis of BD is poorly understood and evidence supporting a role for primed neutrophils in BD-associated thrombotic risk is scant. To respond to inflammatory insults, neutrophils release web-like structures, known as neutrophil extracellular traps (NETs), which are prothrombotic. We evaluated the role of NETs and markers of NETs in BD.MethodsBlood samples were collected from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
98
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 33 publications
5
98
0
4
Order By: Relevance
“…We know that colchicine, anti-TNF (tumor necrosis factor), and anti-interleukin 6 drugs, which have been already used in BD treatment, cause a decrease in NET formation. 10 Potential other medicines such as N-acetyl-cysteine, PAD4 inhibitor, or DNase I that directly target circulating NETs could also be tried. 31 32 33 However, the efficacy and safety data for novel NET inhibitors are deficient.…”
Section: How To Test This Hypothesismentioning
confidence: 99%
See 3 more Smart Citations
“…We know that colchicine, anti-TNF (tumor necrosis factor), and anti-interleukin 6 drugs, which have been already used in BD treatment, cause a decrease in NET formation. 10 Potential other medicines such as N-acetyl-cysteine, PAD4 inhibitor, or DNase I that directly target circulating NETs could also be tried. 31 32 33 However, the efficacy and safety data for novel NET inhibitors are deficient.…”
Section: How To Test This Hypothesismentioning
confidence: 99%
“…Venous inflammation and neutrophil hyperfunction are the hallmarks of BD pathogenesis. 9 10 11 Veins are a primary location for inflammation in BD patients, although the etiology of venous predilection remains unknown. Both Seyahi et al 11 and Alibaz-Oner et al 9 demonstrated that vein wall thickness increased among BD patients, even in the absence of evident vascular involvement.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The controlled mechanism of NE delivery consists of either the release of granules into a phagolysosome where microbes are degraded or exocytosis of the azurophil into extracellular spaces [20]. Uncontrolled release of NE can also be due to necrosis and/or NET activation and release (NETosis) [20,21]. Neutrophil degranulation can be triggered by various inflammatory factors or direct contact with the extracellular matrix (ECM) [22], and increased neutrophil recruitment can extend the duration of inflammation [23].…”
Section: Introductionmentioning
confidence: 99%